An illustrated key to the genera of Thripinae (Thysanoptera) from India - Dey, Soumi; Datta, Anindita; Mandal, Sandip; Kumari, Shruti; Kumar, Vikas; Tyagi, Kaomud (Zootaxa, 2026)
An identification key is provided for 86 genera of subfamily Thripinae from India. Photographs are provided of each character used in this study, also, wherever possible, notes on host-plant associations and geographical distributions. Ajothrips medius Bhatti is considered a syn. nov. of A. gara Bhatti. In addition, Smeringothrips salaciae Priesner is redescribed, and the male of this species is described for the first time.